Identification of Gyromitra infula: A Rapid and Visual Method Based on Loop-Mediated Isothermal Amplification - Xie, Xiaomei; Li, Bu; Fan, Yuguang; Duan, Renhe; Gao, Chonghua; Zheng, Yuan; Tian, Enjing (Frontiers in Microbiology, 2022)
With mushroom poisoning emerging as one of the most serious food safety problems worldwide, a rapid identification method of poisonous mushrooms is urgently required to investigate the source of poisoning. Gyromitra infula, a kind of poisonous mushroom, contains gyromitrin toxin, which causes epileptogenic neurotoxicity and hemolytic disease. This study aimed to establish a rapid and visual method of G. infula identification based on loop-mediated isothermal amplification (LAMP). A set of specific LAMP primers was designed, and its specificity in G. infula was confirmed against various mushroom species, including its closely related species and other macrofungi. The sensitivity assay showed that the minimum concentration of genomic DNA detected by LAMP was 1 ng/μl. The method’s applicability was conducted by preparing mushroom samples that were boiled and digested in artificial gastric juice. The results showed that the content as low as 1% G. infula can be successfully detected. This method can be completed within 90 min, and the reaction results can be directly observed by the naked eyes. Hence, the identification method of G. infula established based on LAMP in this study is accurate, rapid, sensitive, and low-cost, which is required for clinical treatment or forensic analysis when mushroom poisoning occurs.